2019
DOI: 10.1096/fj.201802322rr
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of stress‐associated gene Nupr1 increases bone volume by attenuating differentiation of osteoclasts and enhancing differentiation of osteoblasts

Abstract: Nuclear protein 1 (NUPR1) is a multifunctional stress‐induced protein involved in regulating tumorigenesis, apoptosis, and autophagy. Bone homeostasis is maintained by bone‐resorbing osteoclasts and bone‐forming osteoblasts and osteocytes. We aimed to determine the role of NUPR1 in bone metabolism. Using microcomputed tomography, we found that mice lacking Nupr1 exhibited increased bone volume. Histologic analysis showed that Nupr1 deficiency decreased osteoclast numbers but increased osteoblast numbers and os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Mice tibias without muscle, soft tissue and periosteum were prepared and then removed bone marrow cells by flushing with α-MEM. Osteoblasts on the surface of bone were then collected 43 . Primary osteoblasts were cultured in α-MEM containing 10% FBS for 7 days before experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Mice tibias without muscle, soft tissue and periosteum were prepared and then removed bone marrow cells by flushing with α-MEM. Osteoblasts on the surface of bone were then collected 43 . Primary osteoblasts were cultured in α-MEM containing 10% FBS for 7 days before experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The updated mitochondria content triggers the alteration in membrane permeability resulting in the discharge of cytochrome c, which leads to cell death (20). Other research has elucidated a confirmed association between the deficiency of NUPR1 and bone metabolism, by mediating the receptor activator of nuclear factor kappa-Β ligand or (RANK ligand or RANKL) and sclerostin, which in turn enhances the proliferation of osteoblasts and the downregulation of osteoclasts (22). NUPR1 interacts with and activates SNAP25 to initiate an autolysosomal process that results in premature senescence and autophagy process (17).…”
Section: Nupr1 and Its Potential Role In Cancer And Pathological Conditions (Review)mentioning
confidence: 99%
“…Whilst secretion is elevated by reduced mechanical load, disruption to endo-lysosomal biogenesis and altered hydrolase function may inhibit the efficient endocytosis and degradation of sclerostin, maintaining its inhibitory effects on Wnt signalling pathways. Interestingly, sclerostin expression is induced by Nupr1 via Runx2 transcription factor [71]. Nupr1, a stress-associated gene, is highly expressed in mature osteoclasts; however, Nupr1-deficient mice show elevated autophagy and apoptosis [71], suggesting that Nupr1 is a protective factor in osteoclast homeostasis or that osteoclasts pre-disposed to elevated Nupr1 will survive spaceflight stressors that induce autophagy and apoptosis.…”
Section: Bone Lossmentioning
confidence: 99%
“…Interestingly, sclerostin expression is induced by Nupr1 via Runx2 transcription factor [71]. Nupr1, a stress-associated gene, is highly expressed in mature osteoclasts; however, Nupr1-deficient mice show elevated autophagy and apoptosis [71], suggesting that Nupr1 is a protective factor in osteoclast homeostasis or that osteoclasts pre-disposed to elevated Nupr1 will survive spaceflight stressors that induce autophagy and apoptosis. Investigations on the interplay of stress response, autophagy, and the endo-lysosomal system on sclerostin and osteoclast activity in space environments may reveal new insights to maintaining bone health in spaceflight.…”
Section: Bone Lossmentioning
confidence: 99%